2022
DOI: 10.5114/ceji.2022.124396
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of TREC/KREC detection protocol for newborn SCID screening in Bulgaria: a pilot study

Abstract: Neonatal screening for inborn errors of immunity (IEI), based on quantification of T-cell-receptor- excision circles (TRECs) and kappa-deleting recombination-excision circles (KRECs) from dried blood spots (DBS), allows early diagnosis and improved outcomes for the affected children. Determination of TREC/KREC levels from prospectively collected newborns’ Guthrie cards and from DBS samples of patients with confirmed IEI was done using a commercial kit. Retrospective assessment of flow cytometry eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
1
0
2
Order By: Relevance
“…Both pediatricians and geneticists considered selective WGS as a potential option for improving Bulgarian NBS [ 728 ]. The results of a pilot study demonstrating the feasibility of SCID screening were recently reported [ 729 ]. Cases of arginase deficiency in the Roma area point to the need for ARG screening in this region [ 730 ].…”
Section: Resultsmentioning
confidence: 99%
“…Both pediatricians and geneticists considered selective WGS as a potential option for improving Bulgarian NBS [ 728 ]. The results of a pilot study demonstrating the feasibility of SCID screening were recently reported [ 729 ]. Cases of arginase deficiency in the Roma area point to the need for ARG screening in this region [ 730 ].…”
Section: Resultsmentioning
confidence: 99%
“…При заболеваниях с В-клеточным иммунодефицитом (Х-сцепленная агаммаглобулинемия и общий вариабельный иммунодефицит) высокочувствительны и специфичны показатели KREC, а при аутоиммунных заболеваниях значения KREC коррелируют с активностью процесса и ответом на терапию [58,59].…”
Section: методы изучения иммунитетаunclassified
“…Эти маркеры стали важными -быстрыми, простыми, неинвазивными и относительно недорогими -современными высокочувствительными и специфичными компонентами комплексного неонатального скрининга в составе других тестов и маркеров широкого спектра генетических и метаболических нарушений. Измерение TREC и KREC позволяет проводить скрининг большого числа новорожденных за короткий промежуток времени [53,[59][60][61][62][63][64][65].…”
Section: методы изучения иммунитетаunclassified